Examining harmful impacts of the COVID‐19 pandemic and school closures on parents and carers in the United Kingdom: A rapid review - Hope Christie; Lucy V. Hiscox; Sarah L. Halligan; Cathy Creswell (JCPP Advances, 2022)
Abstract Background As a result of the COVID‐19 pandemic, school closures meant that for many households, home and school environments became intertwined. Parents and carers found themselves taking on the role as de‐facto educators, as well as balancing working from home and caring for additional members of the household. Understanding the full extent of the effects incurred by parents and carers during school closures is vital to identifying and supporting vulnerable families. This rapid review aimed to appraise the available evidence on the potential effects of the COVID‐19 pandemic on UK parents and carers. Methods Searches for academic literature were conducted using Proquest Central, Scopus, and Google Scholar between 21st and 28th April 2021 using search terms describing “parents and carers”, “COVID‐19” and the “UK”. Additional literature was identified on relevant parents and carers' organisations websites including charity reports. Results Thirty‐two articles were found relating to harms affecting parents and carers in the UK High levels of psychological distress, including anxiety and depression, were consistently identified in the general parent population, and especially in parents caring for a child with special educational needs and/or neurodevelopmental disorders (SEN/ND). Charity reports indicated that many parents, especially those from an ethnic minority background and kinship carers, were worse off financially and with food insecurities, whereas empirical evidence showed that mothers were more likely to initiate furlough for themselves compared with fathers or childless women. Domestic abuse support services also reported a sharp rise in demand during lockdown restrictions, and practitioners reported an increase in child and adolescent violence towards parents. Conclusions Given the known impacts of parental stress, mental health problems, domestic violence and financial hardship on children's development, it is critical that these findings are taken into account in case of future pandemics to minimise harms both to parents and their families.